PENDAMPINGAN PEMBUATAN SMART STORINOMIK BILINGUAL BERMUATAN GASTRODIPLOMASI BAGI USAHA SAMBEL PECEL SRIKANDI DI KOTA MADIUN SEBAGAI INTERNASIONALISASI KULINER KHAS NUSANTARA - Saputra, Ardi; Meilasari, Priska; Widdy, Vinsensius (Asawika : Media Sosialisasi Abdimas Widya Karya, 2025)
This community service program focuses on empowering Sambel Pecel Srikandi MSMEs in Madiun City, which have been established for more than 25 years and are known to have distinctive taste quality from hereditary recipes, but still face serious obstacles in aspects of modern marketing and product internationalization. The main problems of the partners can be mapped into three things, namely the low utilization of social media and artificial intelligence technology in promotional strategies, the monotony of marketing content that has not used the storynomics approach, and limited English language skills that make it difficult for products to reach the global market. To answer these challenges, the implementation team designed three main solution patterns that are applicable and sustainable, namely (1) assistance in making social media and training in the use of artificial intelligence to support digital promotions, (2) strengthening storynomics-based marketing techniques with gastrodiplomacy content as a strategy to promote cultural values as well as culinary diplomacy, and (3) training in translating and editing promotional content in English to create bilingual promotions that can reach international audiences. The implementation method is designed through the stages of socialization, training, practice, intensive assistance, technology application, and sustainability evaluation, involving lecturers, students, and partners in an active collaborative manner. The outputs of the activities include increasing the capacity of partners in the field of bilingual digital marketing, creating a minimum of ten gastrodiplomacy-based storynomics promotional contents, scientific publications in Sinta journals, publications in online mass media, audio-visual content on YouTube channels, and promotional posters on social media. Thus, this program not only serves to improve the competitiveness of local MSMEs, but also becomes a concrete strategy to internationalize the culinary specialties of the archipelago, especially pecel Madiun, and supports the achievement of SDGs, Key Performance Indicators (IKU) of universities, and the government's Asta Cita in encouraging downstream and industrialization of local products based on the creative economy).